Peran Anggaran Operasional Sebagai Sarana Perencanaan Dan Pengendalian Laba: Studi Kasus Pada Pt. Wen di Gresik - Diana Zuhroh (AKUNTANSI 45, 2025)
This research was conducted on PT. WEN Gresik by using a qualitative research approach with a descriptive method that has the purpose of finding out the role of the operational budget as a means of planning and controlling profits, with analytical tools using operating budgets and budget realization. The results of the study show that PT. WEN in the process of preparing its operational budget is not precise, planning and controlling the budget is not careful and resulting in projected profits as stated in the budget are difficult to achieve. The solution is to prepare an operational budget well, because with the right budgeting, it is hoped that it will be possible to know the difference between the budget and the realization can occur and how to control it in the future and can be used as a coordination and supervision tool, so that the company's goals that have been determined are easily achieved.